Estimating Stand Carrying Capacity for Three Common Pine Species Across Various Regions of Türkiye - Seki, Mehmet; Yang, Sheng-I; Duyar, Ahmet; Raptis, Dimitrios I.; Atar, Davut; Özkal, Mustafa Kağan; Sakici, Oytun Emre; von Gadow, Klaus (MDPI AG, 2025)
Sustainable management of forest ecosystems requires assessing forest dynamics and project stand growth and yield in order to make strategic decisions. The size–density relationship is one of the most important measures in quantifying the carrying capacity of a forest ecosystem and determining appropriate silvicultural decisions. In this study, the maximum stand density index (SDImax) was estimated for three common pine species in seven different ecological regions across Türkiye. Observations from 14,413 sample plots, including Calabrian pine (Pinus brutia Ten.; 6266 plots from five regions), Black pine (Pinus nigra J.F. Arnold; 6106 plots from five regions) and Scots pine (Pinus sylvestris L.; 2041 plots from three regions) forests were used in this study, covering the entire natural range of these three pine species. A mixed model with region as a random effect was developed for each species to estimate SDImax. Results show that the slope coefficients of the self-thinning lines vary by species and are significantly different from −1.605. The Scots pine stands exhibited the highest SDImax, followed by Black pine and Calabrian pine stands. Across seven ecological regions, the highest SDImax was observed in the Aegean region for Calabrian and Black pine and in the East Anatolia region for Scots pine. The arid Inner Anatolia region yielded the lowest SDImax for Black pine and Scots pine. The humid and semi-humid regions showed a higher SDImax compared to arid regions. The three pine species studied make up almost half of the total forest area in Türkiye. The results of the study are therefore very important in terms of quantitative assessment of the country’s forests. The differences in stand dynamics of these three pine species, which are also widely distributed outside Türkiye under different ecological conditions, may also be a relevant source of information for other regions. Moreover, considering that pine stands in dry environments have a lower carrying capacity than those in humid conditions, it seems likely that pine forests in Türkiye will be affected by increasing global warming.